Transforming Education in Guyana: National Consultation – Final Report: Ministry of Education - Gyuana. Ministry of Education (Ministry of Education, Guyana, 2022)
Global crises and the disruption to education caused by the COVID-19 pandemic have exacerbated the worldwide challenges faced by education sectors in the delivery of quality education and lifelong learning for all. Recognizing the potential adverse impacts that these challenges could engender in the long-term, particularly for the global development agenda, United Nations (UN) Secretary General, António Guterres, will convene a Transforming Education Summit (TES) in September 2022 to mobilize governments and other stakeholders to “renew the global commitment to education as a pre-eminent public good.” The Secretary-General has called on countries to conduct national and sub-national consultations ahead of the TES to mobilize collective action towards achieving SDG 4 (quality education).
Keywords: transforming education; lifelong learning; educational development